SBAs for the final FRCA - Nickells, James; Everett, Toby; Walton, Benjamin (Cambridge : Cambridge University Press, 2010)
This is the first book dedicated to providing exam practice in the new required single best answer question style for the FRCA. It contains 300 single best answer multiple choice questions and advice on how to approach revision and sitting the exam. There are also four 75-question exam papers, each with an answer section containing detailed explanations of the reasoning behind the answer and providing background information about each topic. SBAs for the Final FRCA may be used for examination practice and as a source of knowledge on many of the key topics in the syllabus. From the writing team behind SAQs for the Final FRCA, this book uses a similar style of challenging questions and well researched explanations to help the candidate through the new FRCA written paper. This is an invaluable tool for your exam preparation.
Machine generated contents note: Introduction; FAQs about SBAs for the Final FRCA MCQ; Papers: Paper A; Paper B; Paper C; Paper D; Answers: Paper A; Paper B; Paper C; Paper D; Explanations: Paper A; Paper B; Paper C; Paper D; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Anesthesia -- Examinations, questions, etc